Pulmonary delivery of favipiravir inhalation solution for COVID-19 treatment: in vitro characterization, stability, in vitro cytotoxicity, and antiviral activity using real time cell analysis. (31st December 2022) - Yildiz Pekoz, Ayca; Akbal Dagistan, Ozlem; Fael, Hanan; Culha, Meltem; Erturk, Aybige; Basarir, Nur Sena; Sahin, Gokben; Serhatli, Muge; Cakirca, Gamze; Tekin, Saban; Sen, Leyla Semiha; Sevim, Mustafa; et al.
Abstract: Favipiravir, an RNA-dependent RNA polymerase (RdRp) inhibitor, is used to treat patients infected with influenza virus and most recently with SARS-CoV-2. However, poor accumulation of favipiravir in lung tissue following oral administration has required an alternative method of administration that directly targets the lungs. In this study, an inhalation solution of favipiravir at a concentration of 2 mg mL −1 was developed and characterized for the first time. The chemical stability of inhaled favipiravir solution in two different media, phosphate buffer saline (PBS) and normal saline (NS), was investigated under different conditions: 5 ± 3 °C, 25 ± 2 °C/60% RH ± 5% RH, and 40 ± 2 °C/75% RH ± 5% RH; in addition to constant light exposure. As a result, favipiravir solution in PBS revealed superior stability over 12 months at 5 ± 3 °C. Antiviral activity of favipiravir was assessed at the concentrations between 0.25 and 3 mg mL −1 with real time cell analyzer on Vero-E6 that were infected with SARS-CoV-2/B.1.36. The optimum concentration was found to be 2 mg mL −1, where minimum toxicity and sufficient antiviral activity was observed. Furthermore, cell viability assay against Calu-3 lung epithelial cells confirmed the biocompatibility of favipiravir at concentrations up to 50 μM (7.855 mg mL −1 ). The in vitro aerodynamic profiles of the developed inhaled favipiravir formulation, when delivered with soft-mist inhaler indicated good lung targeting properties. These results suggest that favipiravir solution prepared with PBS could be considered as a suitable and promising inhalation formulation for pulmonary delivery in the treatment of patients with COVID-19.